A randomized, double-blind, placebo-controlled pilot study to assess bacterial anti-adhesive activity in human urine following consumption of a cranberry supplement. Issue 12 (8th November 2019) - Liu, Haiyan; Howell, Amy B.; Zhang, Derek J.; Khoo, Christina
Abstract : Urinary tract infections (UTIs) are one of the common bacterial infections treated with antibiotics. Abstract : Urinary tract infections (UTIs) are one of the common bacterial infections treated with antibiotics. The North American cranberry is recommended for prophylaxis in women with recurrent UTIs as a nutritional alternative. The ability of cranberry components and their metabolites to inhibit adhesion of uropathogenic Escherichia coli ( E. coli ) is an important mechanism by which cranberry mitigates UTIs. The objective of this study was to evaluate urinary anti-adhesion activity against type 1 and P-type uropathogenic E. coli after consumption of cranberry +health™ cranberry supplement (cranberry chew). In this randomized, double-blind, placebo-controlled, crossover design pilot trial ( n = 20), subjects consumed two cranberry or placebo chews, one in the morning and one in the evening. Clean-catch urine samples collected at the baseline and post-intervention (0–3, 3–6, 6–9, 9–12, 12–24, 24–30, 30–36 h) were tested for anti-adhesion effects with a mannose-resistant human red blood cell hemagglutination assay specific for P-type E. coli, or a T24 cell line model for type 1 E. coli . Urinary anti-adhesion activity against P-type E. coli after consumption of the cranberry chew was significantly greater ( p < 0.05) than that observed with placebo chew at all time points except 24–36 h. Ex vivo anti-adhesion effects on type 1 E. coli were greater ( p < 0.05) after cranberry chew consumption than placebo chew at 3–6 and 6–9 h urine collections. In conclusion, consumption of cranberry +health™ cranberry supplement exhibited greater ex vivo urinary anti-adhesion activity compared to placebo, suggesting that it may have the potential to help promote urinary tract health.